2010
DOI: 10.1055/s-0039-1697804
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In-Office and Home Bleaching Gels on the Surface Mercury Levels of Dental Amalgam

Abstract: Objectives:The aim of this study was to evaluate the effect of different in-office and home bleaching gels on the surface mercury levels of dental amalgam.Methods:Sixty disk-shaped amalgam specimens (GS-80, SDI- Australia) were prepared and randomly divided into the following treatment groups: 1. Distilled water (control); 2. 15% home-bleach carbamide peroxide (Opalescence PF, Ultra dent, USA) applied for 6 h/day for 3 weeks; and 3. 35% in-office bleach carbamide peroxide (Opalescence Quick, Ultradent) applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…These authors state that prolonged treatment (more than 14 days) with bleaching agents can promote microstructural changes in the amalgam surfaces, possibly resulting in increased patient exposure to toxic byproducts. Similar results were observed by Oskoee et al [13] who evaluated the effect of CP at 15% applied for 6h/day and observed that Hg levels were significantly higher than control group. At 16% and 30% CP concentrations, Gurgan et al [23] also founded an increase in the Hg release in the samples tested.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These authors state that prolonged treatment (more than 14 days) with bleaching agents can promote microstructural changes in the amalgam surfaces, possibly resulting in increased patient exposure to toxic byproducts. Similar results were observed by Oskoee et al [13] who evaluated the effect of CP at 15% applied for 6h/day and observed that Hg levels were significantly higher than control group. At 16% and 30% CP concentrations, Gurgan et al [23] also founded an increase in the Hg release in the samples tested.…”
Section: Discussionsupporting
confidence: 89%
“…Considering dental amalgam restorations, some studies have shown that the exposure of amalgam to bleaching agents causes an increase in Mercury (Hg) levels on the amalgam surface [12,13], as well as an additional Hg release [14][15][16][17]. Besides, a variation in the Hg release was found among the different types of amalgam exposed to the bleaching agent [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Most tooth bleaching procedures are safe and well-accepted for the treatment of this esthetic problem, as they do not require any reduction in tooth structure. [3][4][5][6][7] The first condition of orthodontic treatment is bonding the orthodontic brackets to tooth surfaces. However, this step is temporary, because the brackets are removed after active treatment, 8 and maintaining a sound, unblemished enamel surface after debonding is the clinician's primary goal.…”
mentioning
confidence: 99%
“…The first esthetic treatment using bleaching agents was reported at the end of 19 th century [2,3]. In our time, whitening process consists in discoloring dentition by exposing it to various oxidizing materials, such as: hydrogen peroxide (H 2 O 2 ) [4][5][6][7][8][9] or H 2 O 2 releasing agents (i.e., carbamide peroxide (CP) [2,[9][10][11][12], and sodium perborate) over a period of time, in order to obtain a lighter color of teeth. CP is a very unstable compound and in contact with tissues and saliva will immediately degrade into about onethird H 2 O 2 and two-thirds urea, being in fact a source of H 2 O 2 [6,13].…”
Section: Introductionmentioning
confidence: 99%
“…In practical life, bleaching agents may come into contact with restorative materials, particularly when using mouth guard bleaching or home kits [4] causing undesirable changes, such as softening and degradation by wear and corrosion of the teeth and/or restorative materials [10,13] prosthetic and implant systems [15]. In this context, extensively research were performed in order to evaluate the surface properties and/or surface alterations of different esthetic restorative materials by different methods, such as: surface roughness measurements [2,4,11]; surface topography evaluation by scanning electron microscopy (SEM) [2,8,11] or by atomic force microscopy (AFM) [7]; profilometric analysis [12]; determination of the alterations in atomic weight by energy dispersive X-ray spectroscopy (EDS) [2,10] or by X-ray photoelectron spectroscopy (XPS) [9]; metal ions release from dental alloys by inductively coupled plasma-mass spectrometry (ICP-MS) [4]; crystallinity index analysis by Raman spectroscopy [5,7]; color measurements by spectrophotometry [5,7]. The corrosion parameters obtained by using electrochemical techniques of investigation of dental metallic alloys in contact with whitening agents are related to the biocompatibility and long-life of different restorative, prosthetic and/or implant systems [4].…”
Section: Introductionmentioning
confidence: 99%